Pazos Alonso, C. (2022). Francisca Wood and Nineteenth-Century Periodical Culture: Pressing for Change. Cambridge: Legenda (Studies in Hispanic and Lusophone Cultures, 35), 250 pp. ISBN 978–1–78188–799–8. - Héloïse Elisabeth Marie-Vincent Ghislaine Ducatteau (Banber Erevani Hamalsarani. Sots'iologia, 2024)
book review